Sunscreen Effect of Andaliman Methanol Extract Nano Gel on The Amount of Melanin in Wistar Rats Exposed to UV-B Light - Vera Vera; Linda Chiuman; Chrismis Novalinda Ginting; Atika Rimalda Nasution; Chrismas Gideon Bangun; Primta Bangun (Poltekkes Kemenkes Tanjung Karang, 2024)
Excessive exposure to UV-B rays can increase melanin production, potentially causing skin damage, making it necessary to prevent this through the use of natural-based sunscreens, such as nano gel from methanol extract of andaliman, to protect the skin from the harmful effects of UV-B radiation. This study aims to evaluate the sunscreen effect of andaliman methanol extract nanogel on the amount of melanin in Wistar rats exposed to UV-B light. The method used was a laboratory experimental study with a randomized posttest only with a control group design using mice as the research subjects. The results of the study showed that the SPF values of andaliman extract at concentrations of 2%, 3.5%, and 5% were 2.11, 2.49, and 2.45, respectively, which are considered low for sunscreen protection standards. Additionally, the amount of melanin obtained from each treatment group was also categorized as small, indicating that the andaliman extract in nano gel form did not significantly reduce melanin production in Wistar rats exposed to UV-B rays. In conclusion, there is no sunscreen effect of andaliman methanol extract nanogel on the amount of melanin in Wistar rats exposed to UV-B light. This could be due to factors such as the low SPF value, the lack of stability of the active ingredients in the nano gel, or the need for an increased dosage. The implications of these findings suggest the need for further research to optimize the formulation or explore other more effective ingredients in preventing melanin production caused by UV-B exposure.